Implicit Elliptic Problems with p-Laplacian - Cabanillas Lapa, Eugenio; Luque Rivera, Jesus Virgilio (Armenian Journal of Mathematics, 2024)
In this research, we will study the existence of weak solutions for a class of implicit elliptic equations involving the $p$-Laplace operator. Using a Krasnoselskii--Schaefer type theorem we establish our result, extending and complementing those obtained by R. Precup, 2020,  and Marino and Paratore, 2021.
Keywords: Implicit Elliptic Problems; Krasnoselskii Theorem; $p$-Laplacian